A Study of Matrilineal Descent from the Perspective of the Tlingit NexA'di Eagles - Campbell, Chris Rabich (ARCTIC, 1989)
The Athapaskans of the boreal forest of northwestern Canada and Alaska and the Indians of the northern Northwest Coast shared a similar social organization. It was based on the division of a group into moieties and/or phratries, tracing matrilineal descent, practicing exogamy, matrilocality, and sharing resources with other affiliate groups. The Sanyaqoan NexA'di Eagle clan was singular among the Tlingit in the early 20th century because they had a third exogamous group, as opposed to the rest of the Tlingit, who had two: the Raven and the Wolf/Eagle. Therefore, they were often scorned socially by their northern cousins. The NexA'di have also been an enigma to anthropologists. Whereas most researchers have identified the NexA'di as being outside the two major divisions, Olson (1967) suggested they represent "Tlingitized" Tsimshian Eagles. Recent research suggests that, instead, it was the Tlingit Eagles who, through division and migration, introduced the Eagle phratry among the Nisga'a. At an earlier time, the NexA'di or a related Eagle group was present among Tlingit "tribes" as far north as Frederick Sound. The Tlingit, specifically the Chilkat, Kake, Stikine, Tongass, and, of course, the Sanya recognize the NexA'di as being an ancient Tlingit clan that originated in southeast Alaska.Key words: matrilineal descent, matriorganization, Athapaskans, Tlingit, NexA’di, Eagle, phratry/moiety, origins Mots clés: filiation maternelle, matriorganisation, Athapaskans, Tlingit, NexA’di, Aigle, phratrie/moitié, origines